Development and Validation of Parental Support Scale of Children’s Sports Training in China: Socio-Ecological Approach - Zheng, Nan; Yang, Ye (Frontiers in Psychology, 2022)
Objectives: To promote Chinese children participation in sports training and acquisition of sports skills, we combined a social ecological research framework with parental support to develop the Parental Support for Children’s Sports Training Scale (PSCSTS). Methods: The scale was initially developed based on literature review, group interviews, and expert evaluations. A complete reliability and validity test was conducted on 1594 parents of primary and secondary schools in Shanghai. Results: The PSCSTS has 37 questions, and exploratory factor analysis has formed ten factors: policy support, parents’ financial support, community support, media support, sports development, school activity participation, parents’ exercise habits, training quality support, development of school sports activities, learning skills . The higher-order models constructed by validated factor analysis fit well (2/df = 2.13, RMSEA = 0.038, RMR = 0.42, GFI = 0.911, CFI = 0.928, IFI = 0.929, TLI = 0.922). Conclusion: The PSCSTS developed in this study based on a social-ecological framework has high reliability and validity and can be used as a comprehensive measure of parental support for their children’s sports training.